Processo de revelação do diagnóstico de HIV para crianças e adolescentes: convergência entre teoria e prática - Zanon, Bruna Pase (2016)
Disclosure of the diagnosis of infection with Human Immunodeficiency Virus (HIV) is configured with a gradual, continuous and progressive process that enables the confirmation of the diagnosis for children and adolescents, who lived until then under the silence. However, there are barriers, as the reluctance of family, and sometimes unpreparedness of health professionals for conducting this process. This study have as aim: lead to collective construction of a disclosure process of HIV diagnosis in the Infectious Diseases Clinic Pediatric. This is a Convergent Care Research (PCA) conducted at the University Hospital of Santa Maria (HUSM) with health professionals working in the specialized service for production data was used three data collection techniques: participant observation, individual interviews and convergence groups. Ethical principles were respected, according to the Resolution 466 / 2012 of the National Health Council. The results of participant observation is that the revelation of the diagnosis occurs at the Infectious Diseases Clinic Pediatric of HUSM, however there is no monitoring of this process. The individuas interviews, allowed understand the meaning of the revelation of the HIV diagnosis, triggers for disclosure of HIV diagnosis, the actors responsible for disclosing the diagnosis of HIV, which strategies to use for disclosing the diagnosis of HIV and limits and possibilities found by health professionals on disclosure of HIV diagnosis. The convergence of group allowed the construction of the action plan to monitor the development process of HIV diagnosis for children and adolescents in a specialized service. On the action plan there are child identification or adolescent and family / caregiver and information about disclosing the diagnosis of HIV and Six Steps to follow this process. 1st step: questions and curiosities that lead to disclosure of HIV diagnosis; Step 2: age revelation of the HIV diagnosis , Step 3: reasons that lead to disclosure of HIV diagnosis , Step 4: actors involved in the development of HIV diagnosis , Step 5 : Include the family in the development of HIV diagnosis , 6th step : developing strategies for the diagnosis of HIV . It is concluded that reveal the diagnosis is a complex task, but possible and necessary, especially rights of children and adolescents living with HIV. Therefore, it is essential the monitoring, from the preparation to reveal until repercussions as responsibility among multidisciplinary team and family. With the elaboration of the action plan, health professionals will be are able to perform and support the family / caregivers in the process revealing the diagnosis of HIV and therefore benefit children and adolescents in treatment adherence and self care.